1998
DOI: 10.1002/(sici)1097-4601(1998)30:9<629::aid-kin4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling study of the oxidation of isobutene

Abstract: This article describes an experimental and modeling study of the oxidation of isobutene. The low-temperature oxidation was studied in a continuous-flow stirred-tank reactor operated at constant temperature (from 833 to ) and pressure with fuel 913 K(1 atm), equivalence ratios from 3 to 6 and space times ranging from 1 to corresponding to 10 s isobutene conversion yields from 1 to 50%. The main carbon containing products were analyzed by gas chromatography. The ignition delays of isobutene-oxygen-argon mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 21 publications
4
35
1
Order By: Relevance
“…[8][9][10][11][12][13] These studies have focused on elucidating the mechanisms for the oxidation and pyrolysis of isobutene. An issue arising from this body of work is the identity of the products arising from the unimolecular decay of isobutene.…”
Section: Introductionsupporting
confidence: 59%
“…[8][9][10][11][12][13] These studies have focused on elucidating the mechanisms for the oxidation and pyrolysis of isobutene. An issue arising from this body of work is the identity of the products arising from the unimolecular decay of isobutene.…”
Section: Introductionsupporting
confidence: 59%
“…Addition of hydroperoxy radical to isobutene leads to 2,2-dimethyloxirane and hydroxyl [53,75]. The major consumption path of 2,2-dimethyloxirane is unimolecular decomposition to 2-methyl-propanal.…”
Section: Reaction Path Analysismentioning
confidence: 93%
“…The latter molecules are known products of isobutene oxidation [53,75] and motivates the inclusion of the low-temperature oxidation chemistry of this molecule into the current kinetic model.…”
Section: Experimental Datamentioning
confidence: 99%
“…Two mechanisms have been proposed by Dagaut and Cathonnet [195] and by Baugé et al [196] to model the oxidation of iso-butene in jet stirred reactors. But, while they aimed at modelling results below 900 K, these two mechanisms considered only high temperature reactions.…”
Section: Table 11mentioning
confidence: 99%
“…In the case of the additions of •HO 2 radicals, the direct formation of oxiranes and •OH radicals has been considered, while in the case of the addition of •H atoms and •OH and •CH 3 radicals the formation of the two adducts has been taken into account. Several studies [192,[195][196]212] have indicated that when temperature increases the adduct cannot be stabilized, but breaks down into decomposition products. A direct addition/decomposition leading to aldehydes (e.g.…”
Section: 4/ Elementary Steps and Associated Rate Constants Specificmentioning
confidence: 99%